Electromagnetic wave scattering by aerial and ground radar objects - Sukharevsky, Oleg I. (CRC Press, Taylor & Francis Group, 2015)
Electromagnetic Wave Scattering by Aerial and Ground Radar Objects presents the theory, original calculation methods, and computational results of the scattering characteristics of different aerial and ground radar objects. This must-have book provides essential background for computing electromagnetic wave scattering in the presence of different kinds of irregularities, as well as Summarizes fundamental electromagnetic statements such as the Lorentz reciprocity theorem and the image principle. Contains integral field representations enabling the study of scatteing in the presence of different kinds of irregularities